A invenção da Barra da Tijuca: a anticidade carioca - Sánchez, Natália Padilha (2009)
This paper analyzes the appearance of the gated communities − phenomenon of the contemporary city − in the Barra da Tijuca district, located in the western part of Rio de Janeiro. This district, occupied from its beginning by high income population, was one of the last frontiers in the expansion of the city. The intensifi cation of its occupation started in the 1970 s, after the implementation the Pilot Plan, elaborated in 1968 by architect Lúcio Costa, according to the premises of Modern Urbanism. Urban planning, associated with the action of the real estate market and the increase in the urban violence, resulted in the decline of the urban nucleus established by Costa and the appearance of the gated communities − in the 1980 s − as the top real estate product. This model of dwelling, characterized by isolated towers in large stretches of land, with vast green areas and leisure facilities, turned the district into the carioca anti-city. resently, Barra da Tijuca is still one of the main areas of expansion in Rio de Janeiro and is a reference in big private developments focused on the high income population.